Minat Mengadopsi E-Wallet dalam Optimalisasi Digitalisasi UMKM - Siti Annisa Wahdiniawati; Ari Apriani; Didin Hikmah Perkasa; Magito Magito (Yayasan Literasi Sains Indonesia, 2025)
This study aims to give consideration to MSME players to adopt E-wallet as a payment system that has an impact on increasing turnover. This research was conducted on consumers who use E-wallets, so as to provide an overview of what consumers want so that they want to shop and use E-wallets in their transactions. The type of research used is explanatory research with descriptive and quantitative approaches. A sample of 145 respondents who are e-wallet users in Jakarta. Data collection was carried out using the questionnaire method where respondents answered questions arranged in the form of choices and question scales using Likert scales. The data analysis used is descriptive analysis and structural model analysis using SmartPLS 3.3 software tools. The results showed that the ease of use variable had a positive and significant effect on the intention to adopt e-wallet, perceived risk had a positive and significant effect on the intention to adopt e-wallet, promotion did not affect the intention to adopt e-wallet, trust did not affect the intention to adopt e-wallet.